Hybrid TiO₂@SiO₂ Green Hydrogel Nanocatalyst for High-efficiency Photocatalytic Oxidation of Ciprofloxacin under UV Irradiation: Experimentation and RSM Optimization - Riad Mansour; Nacer Ferrah; Nurul Hidayati Fithriyah; Irfan Purnawan; Mustapha Chabane; Fadila Zahouane; Chikh Melkaoui (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
A TiO₂@SiO₂ hydrogel nanocomposite was synthesized via a green sol-gel route for the photocatalytic degradation of ciprofloxacin using a UVA/H2O2 system. The catalyst was optimized via RSM (response surface methodology), identifying UVA irradiation (365 nm) and pH of 5.6 as key parameters, achieving >89% degradation within 180. Characterisation confirmed homogeneous TiO₂ dispersion within a porous SiO₂ matrix. Kinetics followed a pseudo-first-order Langmuir–Hinshelwood model, and the catalyst retained high activity over five reuse cycles. This study introduces a UVA-optimized, RSM-guided photocatalytic system using a green-synthesized TiO₂@SiO₂ hydrogel –distinguished by its integrated process design, operational simplicity, and focus on solar-compatible UVA rather than conventional UVC-driven TiO2@SiO2 systems. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).